Pemanfaatan Learning Management System (LMS) Berbasis Moodle dalam Pembelajaran Fisika terhadap Kemampuan Kognitif Siswa - Dari, Ulan; Putri, Rahayu; Silvini, Yaumil; Arivatussaqdiyah, Arivatussaqdiyah (Medan Resource Center, 2024)
The study examines the impact of a Moodle-based Learning Management System (LMS) on students' cognitive abilities at SMA Negeri 1 Ingin Jaya, addressing the issue of relatively low semester exam scores. Despite various learning activities designed to enhance student performance, the cognitive outcomes remained suboptimal. The research employed a quasi-experimental approach with a pretest-posttest control group design, involving class XI IPA 2 as the experimental group and XI IPA 3 as the control group. Data collection was conducted using test questions to assess cognitive abilities, and data were analyzed using an independent sample t-test. The analysis showed a significant difference in cognitive abilities between the control and experimental groups (p = 0.000 < 0.05), indicating that the Moodle-based LMS had a positive impact on students' cognitive performance. The findings highlight the potential of Moodle as an effective tool for improving learning outcomes and suggest its broader adoption in similar educational settings.